Quantitative Study of Residual Oil Distribution during Water Flooding through Digital Core Analysis. (22nd February 2021) - Liu, Xuechao; Ren, Dazhong; Dong, Fengjuan; Nan, Junxiang; Zhou, Ran
Abstract : The character of residual oil formed during water flooding, one important technique to enhance oil recovery, is helpful to further study permeability and recovery in tight sandstone oil reservoirs. In this paper, we take a tight sandstone reservoir in Ordos Basin as the research object and use in situ displacement X-CT scanning technology to analyze the dynamic characteristics of oil during water flooding. Firstly, core pore radius and oil storage space radius were measured from digital cores which are acquired in different water flooding stages by X-CT scanning technology. Secondly, analytical and evaluation methods were established to describe fluid distribution in the pore space of the core in different water flooding stages based on curve similarity. Finally, by numerical results, we analyzed the oil distribution features in the process of water flooding for core samples. In this paper, the oil distribution characteristics during water flooding are revealed based on digital core analysis. Also, a quantitative evaluation method is given to provide theoretical guidance.